Escaping from Existential Nihilism in Chuck Palahniuk’s Fight Club (1996) - Muhammad Naufal Abiyyu; Desvalini Anwar (English Language and Literature, 2023)
This study discusses the Novel Fight Club (1996) by Chuck Palahniuk. This novel tells a story about the effect of chasing perfection over self-destruction and escaping desperation. These problems appear in the main character’s life, also known as The Narrator (Unnamed). In this thesis, the researcher is using two research questions. (1). What are the causes of existential nihilism that exist in the narrator's life? (2). How does the narrator escape existential nihilism to make his life meaningful? To answer these questions, there are several ways. The first way is to understand why existential nihilism appears in the life of the main character, as revealed in the novel Fight Club. The second way is by using the psychoanalysis approach by Sigmund Freud and the existential nihilism theory by Friedrich Nietzsche. The psychoanalysis approach and the existential nihilism theory will be useful for the analysis of the consciousness and unconsciousness of the narrator’s personality and environment and the active and passive nihilism to define the way the narrator tries to escape. This is shown by the narrator’s living his strange monotonous and egalitarian life and his suffering from insomnia.